2021
DOI: 10.1002/anie.202016642
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Directed Approach in Polyoxometalate Synthesis: Formation of a New Divacant Lacunary Polyoxomolybdate [γ‐PMo10O36]7−

Abstract: Polyoxometalates (POMs) have received increasing attention over the last decades for extending their application and properties that originate from novel structures. For the synthesis of a variety of POM structures, multivacant lacunary POMs are key precursors, which are typically synthesized by empirically controlling the complex equilibrium in aqueous solvents. Unfortunately, despite the excellent catalytic and electrochemical properties of "polyoxomolybdates", only one multivacant lacunary species, i.e., [A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…11 Therefore, POMs can be fascinating components to design molecular hybrids with organic molecules and metal nanoclusters that exhibit unique properties and applications. 12,13 In particular, lacunary POMs can act as inorganic multidentate ligands with abundant reactive oxygen atoms. 14 We recently developed synthetic methods for atomically precise Ag nanoclusters ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, POMs can be fascinating components to design molecular hybrids with organic molecules and metal nanoclusters that exhibit unique properties and applications. 12,13 In particular, lacunary POMs can act as inorganic multidentate ligands with abundant reactive oxygen atoms. 14 We recently developed synthetic methods for atomically precise Ag nanoclusters ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[21] After 24 h of hydrothermal reaction at 175 °C, a NMR peak was generated at 2.8 ppm; this indicated that [P 2 Mo VI 5 O 23 ] 6À formed in the solution (Figure 4c). [22] During the whole synthesis process, including before and after the hydrothermal synthesis, the NMR peak of NH 4 -PNM (À 2.5 ppm) was not detected (Figure 4b-g), which indicated that ɛ-Keggin POM did not exist in the liquid phase. According to the reported literatures, [14] reduction of Mo VI -based molybdates in…”
Section: Formation Of ɛ-Keggin Pom-based Zomosmentioning
confidence: 95%
“…The design and synthesis of novel functional POMs are still being the engine to maintain the high level of research and development of POMs chemistry, which greatly broadens their application fields such as ion conduction, capacitor, catalysis, photoelectromagnetic functional materials, and biomedical chemistry. [26][27][28][29][30] Among them, the ion conduction (especially proton conduction) allows POMs to be good candidates for the next generation of excellent solid-state conducting materials. [31,32] Proton conduction, as a common ion conduction, is widely used in proton exchange membrane fuel cells and sensors.…”
Section: Introductionmentioning
confidence: 99%